SISTEM INFORMASI AKUNTANSI PEMBELIAN DAN PENJUALAN BARANG PADA TOKO PASIFIC CELL - Maksum Hakim (Jurnal Ilmiah Sistem Informasi, 2024)
The development of information systems is progressing very rapidly, therefore a lot of data has to be processed and presented in the form of information. So you really need a truly reliable system to solve this problem. It is not easy to complete and create a report using a manual system, therefore almost all the work we do must use data and the work is assisted by computers. The information system for purchasing and selling goods is very important in a company, whether it is a small or large company. This system helps in monitoring goods purchase transactions and sales transactions in the company. In this way, work can also be completed quickly and the results are more accurate compared to manual work methods.